Selective Americium Separation: New Insights into the Complexation of Trivalent f-Elements with SO3-Ph-BTBP - Sauerwein Fynn S.; Sittel Thomas; Geist Andreas; Panak Petra J.; Wilden Andreas; Modolo Giuseppe (EPJ Web of Conferences)
In the Americium selective (AmSEL) process, the N-donor ligand 3,3’,3’’,3’’’-([2,2’-bipyridine]-6,6’-diylbis(1,2,4-triazine-3,5,6-triyl))tetrabenzenesulfonate (SO3-Ph-BTBP) is used to selectively strip Am(III) from a N,N,N’,N’-tetraoctyl diglycolamide (TODGA) containing organic phase loaded with Am(III), Cm(III) and lanthanides (Ln(III)). Fundamental extraction mechanism studies revealed an unusual extraction behavior of heavy Ln(III) and Y(III), which provided the motivation to investigate their complexation with SO3-Ph-BTBP using nuclear magnetic resonance (NMR) spectroscopy and solvent extraction. NMR spectroscopy indicated the formation of the same SO3-Ph-BTBP complex with Lu(III) in 10-3 mol L-1, 1 mol L-1 and 3 mol L-1 DNO3 solution. However, the complexation at high DNO3 concentration is subject to a slower than expected complexation kinetics leading to the conclusion that the unusual extraction behavior is probably related to a kinetics effect rather than an unknown complex species. Kinetics studies using solvent extraction show a slowly increasing extraction of heavy Ln(III) and Y(III) into the organic phase which is attributed to a kinetically inhibited decomplexation of the SO3-Ph-BTBP complexes. This effect is even more pronounced at higher HNO3 concentration. Additionally, combinations of monoand di-methylated TODGA derivatives with SO3-Ph-BTBP were tested, showing a decreasing performance regarding the actinide(III)/lanthanide(III) and Am(III)/Cm(III) separation with increasing degree of methylation.